Ownership and management problems of condominium living - 289070 Nahendran Subramaniam (Sekudai : UTM, 1993)
Since a few years back, condominiums have mushroomed in all parts of Malaysia especially in the city of Kuala Lumpur. Many attracted by the luxury and numerous facilities and services provided by various condominiums, left their old residences for the condominiums. Newspapers have reported frequently, of how speedily condominiums are sold out. Most of them are ignorant of what is in store for them in their new so called 'modern lifestyle' environment. It is but only recently, the various problems relating to the ownership and management of condominiums are brought to light. The writer intends to study these problems in much detail in this project. It is the writer's conscious belief that the ignorance of the law governing subdivided buildings like the condominiums has a role in creating some of the problems. Thus, The Strata Title Act 1985 has been utilised to fork out the legal rights and obligations of the owners of parcels and the management. Problems faced by both the owners and the management (the developer or the management corporation) are highlighted in this project. Finally, the writer proposes the recommendations to resolve some of the problems at the end before concluding.